Changes and threats in the preservation of the traditional Malay landscape - Harun, Nor Zalina; Hj Mohd Ariffin, Noor Aziah; Abdullah, Fadzidah (Malaysian Institute of Planners, 2017)
The cultural landscape is regarded as being of the most complex designs which involve interactions between man, nature, cultural values and the associated built Environment. Issues relating to the degradation of the cultural landscape are often caused by rapid urbanization and industrialization. The traditional Malay Landscape exists through harmoniously balanced interactions between man, nature, and culture together with the traditional house, and contains unique and interesting features that have to be preserved as one of the most important cultural heritage sites. However, the preservation of heritage in Malaysia tends to focus more on architectural buildings rather than adopting a holistic approach that includes the surrounding environment of where the building is located. The absence of such approach has contributed towards the loss of the traditional Malay Landscape. This study highlights the changes and threats to the preservation of the traditional Malay Landscape by focusing on the preservation of a traditional house compound. The research employs a qualitative approach which involves site visits, interviews, and document analysis concerning the research topic. The old Malay villages located in Tumpat, Kelantan and Alor Gajah, Melaka have been selected as case studies. The findings reveal that the changes and threats include four underlying aspects; Unsuitable and inappropriate uses, Ownership Problems, Inadequate fund and consultation and Current development trends. The study concludes that the traditional Malay Landscape is facing numerous changes and threats in terms of its physical characteristics, environmental aspects, and cultural values. In addition, the study reveals that traditional Malay landscape is not seen here as an integrating, holistic concept.